Students in Islamic Education - Dimas Ramdhan; Nazwah Fatimah; Syarifah; Mahwiyah (Penerbit Hellow Pustaka, 2023)
In Islamic education students are individuals who are developing. The term student has a deeper meaning than the mention of students. that is, in the educational process there are individuals who really want students to be active in the teaching and learning process, not educators. The term learner in Arabic is designated by a number of terms, including terms, mutarabbi, muta'allim, mutaaddib, and daris . In the paradigm of Islamic education, students are God's creatures who have a number of basic potentials (nature) that have not yet developed and have not reached the level of maturity, both from the physical, mental-spiritual, intellectual, and psychological aspects. Therefore, he always needs help, assistance, and direction from educators so that he can optimally develop his potential and direct him to maturity. This means that Islamic education does not only improve the academic quality of students, but also is responsible for the formation of the noble character of students.